Using electronic health records to estimate the prevalence of agitation in Alzheimer disease/dementia. (27th December 2018) - Halpern, Rachel; Seare, Jerald; Tong, Junliang; Hartry, Ann; Olaoye, Anthony; Aigbogun, Myrlene Sanon
Abstract : Background: Agitation is a common neuropsychiatric symptom of Alzheimer disease (AD). Data are scarce regarding agitation prevalence among community‐dwelling patients with AD. Objective: To estimate agitation prevalence in a sample of US patients with AD/dementia overall and by AD/dementia disease severity, using data from electronic health records (EHR). Methods: This retrospective database study examined community‐dwelling patients with ≥1 EHR record indicating AD/dementia from January 2008 to June 2015 and no evidence of non‐Alzheimer dementia during the 12‐month preindex and postindex periods. Agitation was identified using diagnosis codes for dementia with behavioral disturbance and EHR abstracted notes records indicating agitation symptoms compiled from the International Psychogeriatric Association provisional consensus definition. Results: Of 320 886 eligible patients (mean age, 76.4 y, 64.7% female), 143 160 (44.6%) had evidence of agitation during the observation period. Less than 5% of patients with agitation had a diagnosis code for behavioral disturbance. The most prevalent symptom categories among patients with agitation, preindex and postindex, were agitation (31.4% and 41.3%), falling (22.6% and 21.7%), and restlessness (18.3% and 23.3%). Among the 78 827 patients (24.6%) with known AD/dementia severity, agitation prevalence was 61.3%. Agitation during the observation period was most prevalent for moderate‐to‐severe and severe AD/dementia (74.6% and 68.3%, respectively) and lowest for mild AD/dementia (56.4%). Conclusions: Agitation prevalence was 44.6% overall and 61.3% among patients with staged AD/dementia. Behavioral disturbance appeared to be underdiagnosed. While agitation has previously been shown to be highly prevalent in the long‐term care setting, this study indicates that it is also common among community‐dwelling patients.